Optimised dairy cow feeding economy in Hungary - Halász, András; Jónás, Edit (Applied Studies in Agribusiness and Commerce, 2014)
High yielder cows optimal feeding is always a major question in farm management. We attempted to find the optimal yield- and weight group in a Holstein_Freisian herd. Handled more than 2000 milk record samples and concluded that the optimal body weight is about 600-650 kg. Also step up from medium yielder to high yielder is more cost efficient than pushing the milk production over 30 kg milk daily. Our results show that fitness traits and body scores are major factors and every 50 kg of extra weight rises the forage cost in average of 0,11 €cents. The mid-weight cows produce 25 kg of milk daily but the herds are very heterogeneous. The solution should be smaller cows, homogeneous herds and optimized feeding.